The Implementation of Genre Based Approach in the Teaching of Writing at SMPN 7 Jember - Lailatul Hidayah; Budi Setyono; Zakiyah Tasnim[ (FKIP e-PROCEEDING, 2017)
Abstract: Writing is one of the English skills that should be mastered by the English as a foreign language students. It is not an easy task for the English teachers to teach writing to the EFL students, as it requires the English teachers to consider what approach they are going to apply in classroom. One of the approaches that is suggested by the Ministry of Education is genre-based approach. This article as the summary of the thesis entitled The Implementation of Genre Based Approach in the Teaching of Writing at SMPN 7 Jember discussed how the teacher implements genre-based approach in the teaching of writing. This research belongs to descriptive case study that was intended to describe in details the implementation of genre-based approach in the teaching of writing at SMPN7 Jember done by the English teacher. It included how the teacher designs the teaching of writing using genre-based approach, how the teacher implements the genre-based approach in the teaching of writing in the classroom, how the teacher delivers feedback to the students, and how the teacher gives score to the students. The data of the research were analyzed using thematic analysis and the results were reported descriptively. The research result showed that the teacher implemented the four stages of genre-based approach. Those are Building Knowledge of the Field, Modeling of the text, Joint Construction of the Text and Independent Construction of the Text. The finding was highly expected to be an evaluative finding for the teacher and she was suggested to make variation of the teaching strategy to the different types of genre.Keywords: Genre Based Approach, Teaching Writing, Feedback, Scoring System, Thematic Analysis.